Development of interactive learning media based on socio-scientific issues using Smart Apps Creator in the role of viruses for tenth graders - Dewi Diharjo; Umi Fatmawati; Baskoro Adi Prayitno (University of Muhammadiyah Malang, 2025)
The role of virus is an essential material that is not discussed completely in the lesson because of the limited information presented in the reference book. The role of viruses is important to learn because it can increase knowledge and know the role of viruses in life. This research aims to (1) develop interactive learning media based on Socio-Scientific Issues (SSI) using Smart App Creator in role viruses’ material for class x senior high school students, (2) test the validity and practicality of interactive learning media based on Socio-Scientific Issues (SSI) using Smart App Creator for class x senior high school students. The research design used Research and Development (R&D), approach ADDIE development model. The research population used was 10th grade at SMA Negeri 1 Surakarta academic year 2024/2025. Validation data were collected from biology learning media expert, biology content expert, as well as feedback from practitioner and students. The results of the validity of the developed media were 93% (very valid) from media experts and 95% (very valid) from material experts. While the practicality response of the developed media was 82% from biology teachers, 89% from student responses in limited testing and 81% from student responses in field testing and it is concluded to very practical category. Overall, the interactive learning media has been developed is declared valid and practical to be used as a biology learning media in role of the viruses for class x senior high school.